Identify the second step in solving this equation for y : −3(y + 6) = 21 . (1 point)

Responses

Subtract 6 from both sides.
Subtract 6 from both sides.

Divide both sides by −3.
Divide both sides by negative 3.

Divide both sides by 6.
Divide both sides by 6.

Add 6 to both sides.

1 answer

To solve the equation \(-3(y + 6) = 21\), let’s go through the steps.

  1. The first step would typically be to divide both sides by \(-3\) to eliminate the coefficient in front of the parentheses. \[ \frac{-3(y + 6)}{-3} = \frac{21}{-3} \] This simplifies to: \[ y + 6 = -7 \]

  2. The second step would be to subtract \(6\) from both sides to isolate \(y\): \[ y = -7 - 6 \] This gives: \[ y = -13 \]

Therefore, the correct response for the second step is: Subtract 6 from both sides.

Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions